Arogansi Menurut Al-Qur’an: Studi Al-Qur’an Tematik dengan Pendekatan Grounded Theory - Siska Adelia Zahra; Muhammad Alif (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Arrogance, referred to in the Quran as kibr, takabbur, or istikbār, is a serious moral issue with spiritual, social, and political dimensions that require careful consideration. Pride is a major obstacle in accepting divine truth and can contribute to the collapse of the social order, as depicted in the stories of Pharaoh, Qarun, and Iblis. In the modern context, pride appears in various complex forms, including intellectual pride, political dominance, economic inequality and exclusivism. It has also evolved into a structural problem that causes discrimination, marginalization of minority voices, and global tensions. This study analyzes the concept of pride in the Qur'ān using a theoretical approach rooted in themes. This qualitative methodology allows for the development of inductive theories directly drawn from the sacred text. This approach overcomes the limitations of previous research, which is often fragmentary and descriptive. Through open, axial, and selective coding of Qur'anic verses and stories about pride, this study will reconstruct the definition, forms, and characteristics (cognitive, affective, and behavioral) of pride, as well as its consequences in this world and the hereafter. The results show that pride manifests in actions such as belittling others, boasting of self and wealth, rejecting the truth, and showing physical arrogance.